Intraocular lens implantation for patients with coloboma of the iris - LI, JUANJUAN (D.A. Spandidos, 2014)
The aim of this study was to analyze the techniques for intraocular lens (IOL) implantation in patients with coloboma of the iris. A retrospective cohort study was used to analyze the degree of iris coloboma and the characteristics of the crystalline lens in 56 patients with iris coloboma. The patients with a lesser degree of coloboma of the iris and an intact lens capsule were treated by iris suture and IOL implantation into the posterior chamber. Patients with an iris coloboma confined to one quadrant, severe iris atrophy and significant lens capsule coloboma were treated with an annular suture at the edge of the pupil and IOL implantation into the anterior chamber. Patients with a greater degree of iris coloboma and an intact lens capsule were treated with an artificial iris and IOL implantation. The patients were followed up for between five months and five years after surgery. Data relating to vision, photophobia, IOL location, postoperative complications and treatment were also obtained at follow-up. The vision of the patients was improved to varying degrees following the surgery, with the exception of those with amblyopia or serious corneal scars. The photophobia of the patients had also improved. The patients’ levels of satisfaction and comfort were deemed to be satisfactory. Early postoperative complications included hyphema, increased intraocular pressure and uveitis. However, serious complications such as corneal decompensation and IOL dislocation were not observed. Various techniques for IOL implantation were selected based on the degree of iris and lens capsule coloboma; these techniques were capable of improving the vision and photophobia of the patients.